A bibliometric study on Sordariales fungi covering genetic diversity, ecological interactions and biotechnological applications - N.F. Wulandari; A.R. Syam; L. Alhamd; B. Gunadi; Yosmaniar; E. Widjaja; B.N. Utomo; S. Wahyuwardani; R. Widiastuti; T. Kadarini; D. Safar (Global Journal of Environmental Science and Management, 2025)
The kingdom fungi, with its vast diversity and applications, is crucial in maintaining ecosystem balance and supporting industries like food production and environmental protection. Despite their ecological value, research on Sordariales is limited compared to other fungal orders. The objectives are to map the landscape of Sordariales research, identify key themes and gaps, and highlight potential biotechnology applications. The data retrieval from Scopus from 1978 to 2024 for various aspects of Sordariales, including agricultural, nutritional, and industrial dimensions. Strategically chosen search terms were applied across all fields, including titles, abstracts, and keywords, then filtered to the inclusion of the latest relevant literature and underwent an in-depth bibliometric analysis utilized visualization of similarities (version 1.6.20) and the bibliometric R package. Publication trends with minimal research output were recorded until the 1990s, and an increase starting in 1995, which was widely published in high-impact journals with the top journals. Sordariales studies emphasize its ecological, genetic, and industrial importance across multiple scientific fields. The global distribution of research on Sordariales highlights China leading, followed by the United States. Research pattern shows the first cluster was fungal ecology and microbial diversity, the second cluster delves into the genetic and molecular biology of Sordariales, and the third cluster centers on the biochemical and enzymatic properties of Sordariales, despite emerging research assisting researchers in recognizing key trends and future directions. Biotechnological applications show that the carbon and nitrogen-related functions of Sordariales play a significant impact in converting livestock waste into compost, bio-based products, or biofuels, potentially reducing the environmental impact of animal farming, soil health, and nutrient availability, which are essential for plant growth and microbial community dynamics. Soil-related function highlights Sordariales fungi's significant role in soil ecosystems, underscoring their interactions with other microorganisms and their impact on nutrient cycling.  Sordariales contribute to soil health by decomposing organic matter, recycling nutrients, and supporting biogeochemical cycles, thus aiding ecosystem stability. Fermentation and enzymes showcase their metabolic diversity and biotechnological potential. Plant-root related function reveals significant linkages between Sordariales and plant-root functions. Meanwhile, enzymes break down cellulose into simple sugars, facilitating nutrient cycling and enhancing soil fertility. Co-occurrence analysis of Sordariales identified major clusters-fungal ecology, molecular genetics, biochemistry, and phylogenetics-reflecting interconnected research themes and highlighted genetic studies, soil functions, and enzyme applications. Sordariales’ roles in carbon and nitrogen cycling, enzyme production, and plant interactions. Future research should expand data sources and explore molecular mechanisms, as Sordariales fungi are vital for ecological processes and innovative biotechnological applications.